Meningkatkan Layanan Pendidikan Dengan Program Bimbingan Belajar Tambahan Bagi Anak-anak Desa Pulantan - Amalia Putri; Hana Aulia; Juli Nur Jannah; Muhammad Husein; Nor Hayati; Nor Maliah; Ita (Aisha Edutama, 2024)
Education is something important and must be owned by everyone. Everyone has the right to get a decent education. Students have an important role in society. Through this Real Work Lecture (KKN) program, students can practice and apply their knowledge to village communities, especially in the field or education. This article refers to